Measuring Commodity-Level Trade Costs in Asia: The Basis for Effective Trade Facilitation Policies in the Region - Shintaro Hamanaka; Romana Domingo (Asian Development Bank (ADB), 2012)
As tariffs are increasingly being reduced, trade economists and policymakers have begun to emphasize the importance of reducing non-tariff trade costs to facilitate international trade flows. However, the measurement of trade costs and transport costs, in particular, is not an easy task. For developing country policymakers, it is important to accurately understand their country's trade facilitation status (improvement as well as deterioration) at the commodity level, to be able to design appropriate trade facilitation policies. However, in reality, the majority of policymakers and researchers tend to overuse data from the World Bank's Doing Business Report, despite the fact that data on costs to export and import under its trading-across-borders component have several inherent weaknesses. In this paper, we suggest that the use of trade statistics calculated in conjunction with Doing Business data is helpful in understanding overall as well as detailed commodity-level trade costs. The two can be regarded as alternative indicators of trade efficiency, because both indicators improve when the trade transaction is streamlined. Moreover, by using trade statistics, we can compute not only long-term trade costs but also trade costs for each commodity group, unlike the case of Doing Business data where the assumption of a standardized 20-foot, 10-ton dry cargo of a country's leading export or import product is employed. Based on commodity-level trade costs, more concrete trade facilitation policies targeting specific sectors can be developed.
hdl:11540/1305
Keywords: F13; F14; F15; 330; transport costs; commodity level; trade statistics; c.i.f.-f.o.b.; trade facilitation; Transportkosten; Transaktionskosten; Außenhandel; Nichttarifäre Handelshemmnisse; Handelsliberalisierung; Asien